2023
DOI: 10.1038/s41591-023-02405-5
|View full text |Cite
|
Sign up to set email alerts
|

Penetrance of pathogenic genetic variants associated with premature ovarian insufficiency

Abstract: Premature ovarian insufficiency (POI) affects 1% of women and is a leading cause of infertility. It is often considered to be a monogenic disorder, with pathogenic variants in ~100 genes described in the literature. We sought to systematically evaluate the penetrance of variants in these genes using exome sequence data in 104,733 women from the UK Biobank, 2,231 (1.14%) of whom reported natural menopause under the age of 40. We found limited evidence to support any previously reported autosomal dominant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Premature Ovarian Insufficiency. Premature ovarian insufficiency (POI) develops the breakdown of ovarian function and menopause before the age of 40, affects about 1% of women, and is one of the main causes of female infertility [55]. A crosssectional study showed fatigue was a highly prevalent symptom closely associated with menopause in the recruited Chinese women with POI [56].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Premature Ovarian Insufficiency. Premature ovarian insufficiency (POI) develops the breakdown of ovarian function and menopause before the age of 40, affects about 1% of women, and is one of the main causes of female infertility [55]. A crosssectional study showed fatigue was a highly prevalent symptom closely associated with menopause in the recruited Chinese women with POI [56].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Amongst seventy families that underwent extensive genetic analysis, two siblings were compound heterozygous for two missense variants in ELAVL2 . This is an intriguing link given the requirement for Elavl2 in oogenesis [ 45 , 48 ], but given the large amount of genetic heterogeneity, further families are likely needed to confirm this as a causative Mendelian gene for POI [ 59 ].…”
Section: Elavl2 and Its Relevance To Diseasementioning
confidence: 99%
“…Genetic predisposition and chromosomal abnormalities, including fragile-X syndrome, Turner syndrome, and X structural abnormalities or X aneuploidy, are common causes of POI. The genetic cause of POI is often single-gene disorders, with pathological variations in about 100 genes documented in the academic literature [ 1 , 6 , 7 ]. These genes are implicated in various biological processes such as development (Wilms tumor, type 1 = WT1 ; nuclear receptor subfamily 5, group a, member 1 = NR5A1 ), meiosis (helicase for meiosis 1 = HFM1 ; mutS homolog 4 = MSH4 ; DNA meiotic recombinase 1 = DMC1 ; tubulin β 8 class VIII = TUBB8 ), follicle development (bone morphogenetic protein 15 = BMP15 ; newborn ovary homeobox = NOBOX ; specific bHLH transcription factor for folliculogenesis = FIGLA; forkhead box L2 = FOXL2 ), hormonal signaling ( FSH , FSH receptor = FSHR; luteinizing hormone subunit β = LH ; LH receptor = LHR ), metabolism (mitochondrial leucyl-tRNA synthetase 2, mitochondrial = LARS2), and immune regulation (autoimmune regulator = AIRE ) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%